Miopía y factores asociados en los habitantes de la ciudadela Estancia Norte de la ciudad Loja - Ontaneda Salazar, Brenda Michelle (2022)
Refractory defects, such as myopia, are one of the main concerns worldwide in relation to the quality of vision of the population, however, this has not been given the relevant relevance to prevent and treat it in a timely manner. For this reason, the objective of the research was to determine the prevalence of myopia and associated factors in the inhabitants of the Citadel Estancia Norte, in the city of Loja, between April 2020 and March 2021. A descriptive-analytical study was achieve, applied in 134 inhabitants of the Ciudadela Estancia Norte. A previously validated form was used for data collection; the Snellen table was used in the visual acuity assessment. The results showed that the most affected gender was the male with 54% and that the family history of wearing lenses (79%) was the factor that most predisposed to the decrease in visual acuity (53%). The right eye was the most affected with 56%, while the most frequent symptom was blurred vision with 10%, outdoor activity with 54%, 31% eye infections and 14% prematurity. It was concluded that more than half of the analyzed population presents problems of myopia, whence it is necessary to monitor and control